2007
DOI: 10.1186/1471-2458-7-299
|View full text |Cite
|
Sign up to set email alerts
|

Leisure and religious activity participation and mental health: gender analysis of older adults in Nepal

Abstract: Background: Involvement in activities has been found to be beneficial for improving quality of life and successful aging for older adults. Little is known, however, about the involvement in activities and depression of older adults in Asian developing countries. This study explores whether participation in leisure social and religious activities are related to depression and satisfaction with life in older adults of Nepal. Gender differences are also explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 59 publications
4
67
0
4
Order By: Relevance
“…Although activity restriction (e.g., Williamson & Shaffer, 2000) and infrequent participation in social and leisure activities (e.g., Adams et al, 2004; C. T. Lee et al, 2012) are associated with depression in older adults, engagement in activities is related to greater psychological well-being (e.g., Gautam, Saito, & Kai, 2007;Jenkins, Pienta & Horgas, 2002;Pressman et al, 2009) and may mediate the negative impact of functional limitations on depression (Benyamini & Lomranz, 2004). The empirically demonstrated inverse relation between activity engagement and mental health outcomes in later life adds further support to the applicability of behavioral models for the development and treatment of LLD.…”
Section: Behavioral Perspectives On Lldmentioning
confidence: 99%
“…Although activity restriction (e.g., Williamson & Shaffer, 2000) and infrequent participation in social and leisure activities (e.g., Adams et al, 2004; C. T. Lee et al, 2012) are associated with depression in older adults, engagement in activities is related to greater psychological well-being (e.g., Gautam, Saito, & Kai, 2007;Jenkins, Pienta & Horgas, 2002;Pressman et al, 2009) and may mediate the negative impact of functional limitations on depression (Benyamini & Lomranz, 2004). The empirically demonstrated inverse relation between activity engagement and mental health outcomes in later life adds further support to the applicability of behavioral models for the development and treatment of LLD.…”
Section: Behavioral Perspectives On Lldmentioning
confidence: 99%
“…Older adults (N=3,387) in these studies self reported that religion played an important role in their general quality of life. 21,22,23,24 In a study exploring whether participation in religious activities are related to satisfaction with life and depression, a convenience sample of community-dwelling older adults (N=489) in Nepal reported that these activities helped them coping with depression, increased sociability and decreased levels of depression in men who prayed more (GAUTAM et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Nepal has a high proportion of male migrant workers, and being a migrant worker can lead to mental health problems [28]. However, migration of husbands and partners can have an impact on the mental health and suicide risk of the women staying behind [29].…”
Section: High Rate Of Male Migrationmentioning
confidence: 99%